2004
DOI: 10.1080/03081070310001633572
|View full text |Cite
|
Sign up to set email alerts
|

Integration of human knowledge and measured data for optimization of fabric hand

Abstract: This paper presents a new method for modeling the relationship between objective and subjective fabric hand evaluations and between adjusting parameters of fabric production and objective fabric hand features. In this method, fuzzy techniques, principal component analysis and other data analysis techniques are applied and human knowledge on fabric production and numerical data measured on instruments are used in a complementary way for selecting relevant physical features and extracting fuzzy rules. The effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 8 publications
(8 reference statements)
0
15
0
Order By: Relevance
“…They had issued 15 terms. The aim of this study was to correlate process parameters to expert evaluation by the use of fuzzy techniques (Zeng, Koehl, Sahnoun, Bueno, & Renner, 2004).…”
Section: Sample Handling and Termsmentioning
confidence: 99%
“…They had issued 15 terms. The aim of this study was to correlate process parameters to expert evaluation by the use of fuzzy techniques (Zeng, Koehl, Sahnoun, Bueno, & Renner, 2004).…”
Section: Sample Handling and Termsmentioning
confidence: 99%
“…The first part ( VA k ) of the ranking criterion is determined with the aid of the human knowledge 20. As shown in Fig.…”
Section: Input Variable Selectionmentioning
confidence: 99%
“…A method for modelling the relationship between objective and subjective fabric hand evaluations and between adjusting parameters of fabric production and objective fabric hand features has been further proposed [18]. The present authors have also suggested an intelligent system for supporting the design of fashion oriented personalised garments.…”
Section: Introductionmentioning
confidence: 96%